Regulation of Macrophage Polarization by RON Receptor Tyrosine Kinase Signaling - Chaudhuri, Amitabha (Frontiers in Immunology, 2014)
The M1 and M2 states of macrophage polarization are the two extremes of a physiologic/phenotypic continuum that is dynamically influenced by environmental signals. The M1/M2 paradigm is an excellent framework to understand and appreciate some of the diverse functions macrophages perform. Molecular analysis of mouse and human macrophages indicated that they gain M1 and M2-related functions after encountering specific ligands in the tissue environment. In this perspective, I discuss the function of recepteur d’origine nantais (RON) receptor tyrosine kinase in regulating the M2-like state of macrophage activation Besides decreasing pro-inflammatory cytokine production in response to toll-like receptor-4 (TLR4) activation, macrophage stimulating protein (MSP) strongly suppresses nitric oxide synthase (NOS) and at the same time upregulates arginase, which is the rate limiting enzyme in the ornithine biosynthesis pathway. Interestingly, RON signaling preserved some of the characteristics of the M1 state, while still promoting the hallmarks of M2 polarization. Therefore, therapeutic modulation of RON activity can shift the activation state of macrophages between acute and chronic inflammatory states.